Time marker of 137Cs fallout maximum in lake sediments of Northwest China. (1st August 2020) - Lan, Jianghu; Wang, Tianli; Chawchai, Sakonvan; Cheng, Peng; Zhou, Kang'en; Yu, Keke; Yan, Dongna; Wang, Yaqin; Zang, Jingjie; Liu, Yujie; Tan, Liangcheng; Ai, Li; et al.
Abstract: Caesium-137 ( 137 Cs) has no natural source and is commonly employed in establishing the chronology of recent lake sediments in the Anthropocene epoch. Because of their location in the northern mid-latitude Westerlies circulation region, downwind of the Chernobyl accident and their proximity to the Lop Nur Chinese Nuclear Testing (CNT) site, lake sediments in NW China record a 137 Cs fallout maximum of global atmospheric thermonuclear weapon tests (GTWT) in 1963–1964 Common Era (CE), with probably local fallout subpeaks due to the Chernobyl accident in 1986 CE and CNT in 1976 CE. This complexity means that the use of 137 Cs fallout maximum in lake sediments as a time marker in NW China is thus far not well constrained, impeding assessment of recent and future changes in paleoclimate and human activities. To identify the 137 Cs time marker and provide a reliable chronology of surface lake sediments for investigating paleoclimatic changes and for defining the Anthropocene epoch in NW China during the last 50–100 years, here we describe chronologies of 6 near-surface sediment cores from NW China based on 137 Cs and 210 Pb activities, and review the chronology of 23 lake sediments and 10 ice cores from NW China and central Asia based on 137 Cs, 210 Pb, 239+240 Pu, 3 H, 241 Am, and beta-activity dating methods, and annual layer counting, as well as 240 Pu/ 239 Pu isotopic ratios. Based on the potential influence of radioactivity transport from the Chernobyl accident and CNT, and the comparison with deposition records of 26 European lake sediments and 5 Alpine ice cores, we propose that the 137 Cs fallout maximum of lake sediments in NW China and central Asia is primarily attributable to GTWT and that there is no unambiguous evidence to confirm the Chernobyl- and CNT-derived 137 Cs local-fallout subpeaks. Taking into account the approximately one-year delay between injection of 137 Cs into the atmosphere and its incorporation in lake sediment records, we conclude that the 137 Cs fallout maximum in lake sediments of NW China provides a reliable GTWT time marker for 1964 CE. Highlights: 137 Cs fallout maximum in NW China is attributable to the global atmospheric thermonuclear weapon tests in 1963–1964 CE. There is no unambiguous evidence to confirm the Chernobyl- and Chinese Lop Nor-derived 137 Cs local-fallout subpeaks. A delay of ∼1 year between injection of 137 Cs into the atmosphere and its incorporation in lake sediment records.